2018
DOI: 10.17533/udea.rccp.v31n1a04
|View full text |Cite
|
Sign up to set email alerts
|

Ticks and tick-associated spotted fever group Rickettsia from birds in the southwestern Brazilian Amazon

Abstract: Ticks and tick-associated spotted fever group Rickettsia from birds in the Southwestern Brazilian Amazon ¤ Garrapatas y su infección por Rickettsia del grupo de la fiebre manchada en aves del sudoeste de la Amazonía Brasileña Carrapatos e sua infeção por Rickettsia do grupo da febre maculosa em aves do sudoeste da Amazonia BrasileiraAbstract Background: South American birds are known to play a significant role in life cycles of various hard ticks, particularly within Amblyomma genus. However, the tick fauna fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…We found here that Rickettsia infections are common in French Guiana ticks, a pattern also observed among ticks of other South American regions 7,[10][11][12][13]20 . The incidence of infection varied between tick species of French Guiana: 12 of the 22 tick species examined, including Amblyomma, Haemaphysalis and Ixodes species, harbored Rickettsia, and when present, prevalence ranged from 10 to 100%, with significant variations between sampling localities of some species.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We found here that Rickettsia infections are common in French Guiana ticks, a pattern also observed among ticks of other South American regions 7,[10][11][12][13]20 . The incidence of infection varied between tick species of French Guiana: 12 of the 22 tick species examined, including Amblyomma, Haemaphysalis and Ixodes species, harbored Rickettsia, and when present, prevalence ranged from 10 to 100%, with significant variations between sampling localities of some species.…”
Section: Discussionsupporting
confidence: 83%
“…Multilocus typing showed that 11 of these Rickettsia genotypes can be assigned to two validated Rickettsia species, namely R. amblyommatis (two genotypes) and R. bellii (nine genotypes). These two Rickettsia species are widely present among Central and South American ticks, each infecting more than 10 species 7,[11][12][13][21][22][23][24][25][26] . Their presence in French Guiana was therefore expected, but the observation of novel genotypes indicates the presence of important geographic variability: R. amblyommatis and R. bellii have probably radiated within their respective regions, including French Guiana, into different genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present survey broadens the information on ticks infesting birds and related pathogens in two areas from the Atlantic rainforestin Bahia state, northeast Brazil. The mean prevalence and intensity of wild birds infested by ticks was 18.6% and 1.9, respectively, similar to studies from ticks infesting birds in South America, including those conducted in Brazil (Ogrzewalska et al 2011;Luz and Faccini 2013;Flores et al 2014;Ramos et al 2015;Lugarini et al 2015;Luz et al 2017a;Zeringóta et al 2017;Lima et al 2018). In the Atlantic rainforest biome, the prevalence of ticks on birds is from 5 to 18%, with averages between 10 and 13% (Ogrzewalska et al 2009;Luz et al 2012Luz et al , 2017aZeringóta et al 2017).…”
Section: Discussionsupporting
confidence: 82%
“…Another characteristic that was observed in the specimen of this study was the presence of chitinous blades incised in all festoons, characteristic that can be confused with the species A. incisum (Labruna et al, 2005a). In this regard, in a review on the tick species of the state of Acre, Lima et al (2018) suggested that there was a need to confirm the species A. incisum, which may have been confused with the species A. latepunctatum and A. scalpturatum. As so, A. incisum had only been reported once, by Aragão (1936), through examining the material in the Ixodid Collection of the Oswaldo Cruz Institute.…”
Section: Introductionmentioning
confidence: 55%